2021
DOI: 10.3390/biom11081112
|View full text |Cite
|
Sign up to set email alerts
|

How Do Telomere Abnormalities Regulate the Biology of Neuroblastoma?

Abstract: Telomere maintenance plays important roles in genome stability and cell proliferation. Tumor cells acquire replicative immortality by activating a telomere-maintenance mechanism (TMM), either telomerase, a reverse transcriptase, or the alternative lengthening of telomeres (ALT) mechanism. Recent advances in the genetic and molecular characterization of TMM revealed that telomerase activation and ALT define distinct neuroblastoma (NB) subgroups with adverse outcomes, and represent promising therapeutic targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…In IDH wildtype high-risk samples, most of them carry the mutations of PTEN and/or EGFR , which are the characteristics of primary GBMs. The result is consistent with the telomere replacement extension mechanism discussed in previous studies ( Heaphy et al, 2011 ; Akter and Kamijo, 2021 ; Rachakonda et al, 2021 ; Valenzuela et al, 2021 ). This indicates that our signature is capable of identifying the high-risk samples with either primary or recurrent malignant GBM characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…In IDH wildtype high-risk samples, most of them carry the mutations of PTEN and/or EGFR , which are the characteristics of primary GBMs. The result is consistent with the telomere replacement extension mechanism discussed in previous studies ( Heaphy et al, 2011 ; Akter and Kamijo, 2021 ; Rachakonda et al, 2021 ; Valenzuela et al, 2021 ). This indicates that our signature is capable of identifying the high-risk samples with either primary or recurrent malignant GBM characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the uncontrolled confounding by SCA is unlikely to be responsible of the whole difference in survival observed in our study. With regards to telomere maintenance, E2F3 was demonstrated to upregulate the telomerase activity via the RB pathway, 11,57 then a possible role in the deregulation of the telomere maintenance in NB with not‐amplified M YCN and high E2F3 expression cannot be excluded, and deserves further investigation. Other potential limits include the multiple testing bias in stratified analyses, the small sample size in subgroup analyses, which prevents the adjustment by potential confounders, and the insufficient number of events in some subgroups with a consequent lack of statistical power.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence has shown that high TERT expression is associated with poor prognosis [ 11 , 12 , 26 , 31 ], which was also supported by our study. Telomerase represents a promising therapeutic target in NTs, and telomerase‐interacting compounds have been developed [ 32 ]. Recently, BET bromodomain inhibitor OTX015 and carfilzomib (an approved oncology drug) have shown strong synergistic effects to block TERT overexpression and suppressed tumour progression [ 33 ], encouraging the potential use of targeted therapy in patients with TERT ‐rearranged NTs.…”
Section: Discussionmentioning
confidence: 99%